Role of Moringa oleifera seeds and food supplement on some biochemical parameters in male rats - Qader, Rebaz; Yaseen Noori M. AL-Shekhany (Zanco Journal of Pure and Applied Sciences, 2023)
The present study was investigated the antioxidant capacity of Moringa oleifera Seeds (MOS), its impact on the Male Albino rats, and its comparison with Food supplement (FS). The study provided 15 Rats, and according to different feeding foods, the rats are divided into three groups; MOS, FS, and normal Rat's food as a control group. Samples (urine and serum) were collected from each rat after intake MOS, FS and normal food for 85 days then biochemical analysis were performed such as liver enzymes (glutamic oxaloacetic transaminase (GOT), Glutamic Pyruvic Transaminase (GPT), and Alkaline phosphatase (ALP)), lipid profile (high-density lipoprotein (HDL), Triglycerides (TG), and Total Cholesterol (TC)), (Tp and Alb). Moreover, it determined mineral contents of MOS, FS, and normal rat's food by using X-ray fluorescence (XRF). It also detects total antioxidant capacities in MOS, which were evaluated through using 1,1-diphenyl-2-picrylhydrazyl radical (DPPH) assays. Statistical analysis showed the final body weight significantly increased in FS group compared to MOS and control groups. The TP and Alb levels revealed a significant difference between groups in both serum and urine samples. Liver function parameters raised significantly in FS group when compared with Mos and control group. Moreover, it was evaluated of higher concentration of Potassium and Magnesium in MOS when compared with FS group and control group. PPH scavenging capacity in MOS. We conclude that MOS is healthy and rich with Potassium and Magnesium, which can be used as an antioxidant source. While FS has side effects on rats' kidneys and liver, although the FS increases body weight compared to other groups.